The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jora.12245
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Qualification of the Association Between Parenting and Problem Behavior Trajectories Among Mexican‐Origin Father–Adolescent Dyads

Abstract: To address the combined importance of fathers and neighborhoods for adolescent adjustment, we examined whether associations between fathers' parenting and adolescents' problem behaviors were qualified by neighborhood adversity. We captured both mainstream (e.g., authoritative) and alternative (e.g., no-nonsense, reduced involvement) parenting styles and examined parenting and neighborhood effects on changes over time in problem behaviors among a sample of Mexican-origin father-adolescent dyads (N = 462). Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 103 publications
(158 reference statements)
2
45
0
Order By: Relevance
“…Living with family, satisfaction with family relationships, and family connectedness have all been associated with fewer depressive symptoms [7, 29]. Parenting styles can affect mental health, as “reduced involvement” fathering (compared to “authoritative” fathering) was linked to more internalizing and externalizing symptoms among Mexican youth in the United States [32]. Similarly, a history of abuse and neglect from a family member has been associated with symptoms of PTSD, anxiety, and aggression [33, 34].…”
Section: Social Determinants and Mental Health Outcomes: Recent Findingsmentioning
confidence: 99%
“…Living with family, satisfaction with family relationships, and family connectedness have all been associated with fewer depressive symptoms [7, 29]. Parenting styles can affect mental health, as “reduced involvement” fathering (compared to “authoritative” fathering) was linked to more internalizing and externalizing symptoms among Mexican youth in the United States [32]. Similarly, a history of abuse and neglect from a family member has been associated with symptoms of PTSD, anxiety, and aggression [33, 34].…”
Section: Social Determinants and Mental Health Outcomes: Recent Findingsmentioning
confidence: 99%
“…In U.S. Latino families, some researchers report expected negative relations between authoritarian parenting and positive adolescent outcomes, whereas other investigators demonstrate no significant relations between such parenting and outcomes (Domenech Rodríguez et al, 2009). Other research identifies unexpected associations between harsh parenting, demandingness, and Latino youth outcomes (see Halgunseth, Ispa, & Rudy, 2006, for a review), perhaps because scholars are failing to consider these behaviors and dimensions vis-à-vis other aspects of responsiveness (e.g., high acceptance) and demandingness (White et al, 2015; in press). Overall, mixed findings may be interpreted within recent works suggesting that the predominant frameworks may not capture the full range of parenting styles employed by parents of adolescents from diverse groups (Domenech Rodriguez et al, 2009; Kim, Wang, Shen, Hou, 2015; White, Liu, Gonzales, Knight, & Tein, 2016).…”
Section: The Mediating Role Of Prosocial Tendencies In the Relations mentioning
confidence: 99%
“…For example, for immigrant parents with limited income, education, and English skills, the most viable housing options may be in low-rent neighborhoods with high crime rates (Pumariega et al 2005). We therefore highlight two stressors, economic pressure (Mistry et al 2009) and neighborhood disadvantage (White et al 2016), as transcultural stressors that influence the mental health of children of immigrants.…”
Section: Transcultural and Culture-specific Stressorsmentioning
confidence: 99%
“…Therefore, although tiger parenting can result in high academic achievement for adolescents, this may come at the cost of their mental health. For Mexican American families, White et al (2016) found that, for those living in high-adversity neighborhoods, no-nonsense parenting is an adaptive strategy for fathers. This type of parenting allows fathers to recognize the environmental demands of their neighborhoods and adapt their parenting accordingly, resulting in declines in internalizing problems across the course of adolescence in their children.…”
Section: Parental Socializationmentioning
confidence: 99%